Fast Randomized Algorithms for Matrix and Tensor Low-rank Approximation - Hoang, Phong. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Mathematics.; Advisor: Xiaozhe Hu.; Committee: James Adler, and Misha Kilmer.; Keyword: Mathematics.